Factors that contribute to long waiting time for emergency centre patients: a waiting room case study of Paarl hospital, Western Cape - Hardine, Joslyn Magdalene (Stellenbosch : Stellenbosch University, 2017)
Thesis (MCur)--Stellenbosch University, 2017.